2018
DOI: 10.1002/mbo3.620
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Lactobacillus plantarum IBB3036 and Lactobacillus salivarius IBB3154 to persistence in chicken after in ovo delivery

Abstract: The aim of this study was to characterize and compare selected Lactobacillus strains originating from different environments (cow milk and hen feces) with respect to their applicative potential to colonize gastrointestinal track of chickens before hatching from an egg. In vitro phenotypic characterization of lactobacilli strains included the investigation of the important prerequisites for persistence in gastrointestinal tract, such as a capability to survive in the presence of bile salts and at low pH, enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…They play a vital role in animal production due to their non-residual and non-polluting nature. Previous studies have reported the effects of different probiotics in animal diets, such as enhancing the growth rate, increasing feed intake and feed efficiency, improving carcass yield and quality, increasing nutrient digestibility, and controlling enteric pathogens [ 2 , 3 , 4 , 5 , 6 ]. Bacillus , spore-forming bacteria, are becoming increasingly popular as probiotics used in animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…They play a vital role in animal production due to their non-residual and non-polluting nature. Previous studies have reported the effects of different probiotics in animal diets, such as enhancing the growth rate, increasing feed intake and feed efficiency, improving carcass yield and quality, increasing nutrient digestibility, and controlling enteric pathogens [ 2 , 3 , 4 , 5 , 6 ]. Bacillus , spore-forming bacteria, are becoming increasingly popular as probiotics used in animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…The probiotic bacteria should be tolerant to stress factors such as salt and temperature changes, which affect the viability of the bacterial cell. Therefore, the ability to grow in different ranges of salinity and temperature is a positive property in LAB (Aleksandrzak Piekarczyk et al 2018). Hagi et al .…”
Section: Discussionmentioning
confidence: 99%
“…After incubating at 37°C for 3 h, OD 630 was recorded, and the result was expressed based on growth rate (Hosseini et al 2009; Sharifuzzaman et al 2018). To evaluate the effect of salinity and different temperatures, selected LAB isolates were spotted on MRS agar plates containing 2, 4, 6 and8 % (w/v) sodium chloride and incubation at 4, 15, 25, 37 and 45°C for 24 h respectively (Aleksandrzak Piekarczyk et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of different temperatures and sodium chloride concentrations on bacterial survivability were examined according to the procedure described by Mortezaei et al (2020) and Aleksandrzak-Piekarczyk et al (2019), respectively. During temperature treatments, each selected isolate was exposed to different temperatures (37, 45 and 50 C) for 48 h and formation of bacterial colonies was evaluated.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Based on the selection criteria for probiotic strains, a bacterial strain should be able to withstand low gastric pH and bile salts of the intestine, adhere to the intestinal mucosa and exceed safety criteria, such as the absence of haemolytic activity and sensitivity to antimicrobials of human and veterinary importance (Musikasang et al 2009;Iñiguez-Palomares et al 2011). Besides, resistance to osmolytes and temperature is considered as notable features that lead to the successful performance of probiotic bacteria (Salas-Jara et al 2016;Aleksandrzak-Piekarczyk et al 2019) and those candidates which meet the established criteria for probiotic can be used to produce probiotic supplements.…”
Section: Introductionmentioning
confidence: 99%